Pengembangan Game Edukasi Untuk Meningkatkan Kemampuan Spasial Siswa Pada Materi Bangun Ruang Sisi Datar - Susanto; Arif Fatahillah; Saddam Hussen; Muhammad Chaizul Chaqqil Masrur (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2026)
Abstract: Educational games serve as one of the instructional media used by teachers to achieve classroom learning objectives. This study develops a Unity software-assisted educational game to enhance students' spatial abilities in polyhedron geometry. This research aims to produce an educational game that improves students' spatial skills while meeting the criteria of validity, practicality, and effectiveness. The study employs the 4-D development model, consisting of Define, Design, Develop, and Disseminate. The educational game was trialed on 29 students in Class IX C at MTsN 1 Jember. Data were collected through preliminary observations, tests, user response questionnaires, spatial ability questionnaires, and interviews. The developed educational game met the validity criteria based on validation results with a correlation coefficient of 0.95, achieved practicality based on student response questionnaires with a score of 89%, and proved effective in improving students' spatial abilities based on questionnaire and test results, both yielding an average N-Gain score of 0.73. Abstrak: Game edukasi merupakan salah satu media yang digunakan guru untuk mencapai tujuan pembelajaran di kelas. Penelitian ini mengembangkan game edukasi berbantuan software Unity untuk meningkatkan kemampuan spasial siswa pada materi bangun ruang sisi datar. Penelitian ini bertujuan menghasilkan game edukasi yang dapat meningkatkan kemampuan spasial siswa dan menghasilkan game yang valid, praktis, dan efektif. Model penelitian ini menggunakan model pengembangan 4-D yaitu define, design, develop, dan disseminate. Game edukasi ini diujicobakan kepada siswa kelas IX C MTSN 1 Jember dengan jumlah siswa 29. Data dikumpulkan menggunakan observasi awal, tes, angket respon pengguna, angket kemampuan spasial, dan wawancara. Game edukasi yang dihasilkan memenuhi kriteria valid berdasarkan hasil validasi dengan koefisien korelasi sebesar 0,95, praktis berdasarkan angket respon siswa dengan persentase 89%, dan efektif meningkatkan kemampuan spasial siswa berdasarkan hasil angket kemampuan spasial dan hasil tes siswa dengan nilai rata-rata N-Gain sebesar 0,73 dan 0,73.